2003
DOI: 10.1007/s00161-003-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Stack effects on smoke propagation in subway stations

Abstract: In fires of subway stations, the most immediate threat to passengers' life is not the direct exposure to fire, but the smoke inhalation because it contains hot air and toxic gases. To understand the mechanisms driving the motion of smoke is therefore an important issue of fire safety, and the stack effect is found to be an important mechanism having significant influence. In this paper, we compute the three-dimensional smoke flow fields under various fires happened in a representative subway station of Taipei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Besides, hot smokes and fires may damage subway constructions [249]. On the other hand, initial airflows are generated by piston effects or pressure differences and affect later movements of fire smokes in an initial period [250]. For a reasonable and effective evacuation strategy, it is indispensable to study the background airflows in subway microenvironments [20,21].…”
Section: Wind Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, hot smokes and fires may damage subway constructions [249]. On the other hand, initial airflows are generated by piston effects or pressure differences and affect later movements of fire smokes in an initial period [250]. For a reasonable and effective evacuation strategy, it is indispensable to study the background airflows in subway microenvironments [20,21].…”
Section: Wind Environmentmentioning
confidence: 99%
“…Preliminary designs of subway spaces and environmental controls decide the performance of stack effects. Under the same condition, areas and locations of shafts usually predominate airflows, and areas are more dominant than locations [250]. Furthermore, replacing vertical shafts with tilted shafts can eliminate boundary layer separations to optimize smoke exhausts [266].…”
Section: Complex Airflowsmentioning
confidence: 99%
“…In the meantime Merci [8] has concluded that the stack effect becomes stronger as the slope of tunnel increases. Other relevant researches have shown that the stack effect will influence the flame behaviors [11] and the smoke movement will be dominated by the airflow induced by stack effect with the absence of mechanical ventilation [12]. Therefore the smoke movement in an inclined tunnel is different from the one in a horizontal tunnel, which makes it worth studying.…”
Section: Introductionmentioning
confidence: 99%
“…As for this, numerous researchers focus their attention on the fire smoke in subway station throughout the world. Hao [3] investigated the effect of the fire intension and the mechanical exhaust smoke volume on the height of smoke on the platform by the scale-model experiments and numerical modeling simulation; Gao Ran [4] analyzed the effect of the domes on the smoke control in subway station by FDS; Yang H [5] used the method of numerical modeling simulation to study the temperature distribution on the platform with different fire source locations; Meng N [6] studied the efficiency of exhausting with different ventilation mode in fire by FDS; Chen F [7] made simulation and analyzed the properties of smoke flow in different fire scenarios. From above we can see that most research on the fire smoke in subway station is conducted by numerical modeling simulation.…”
Section: Introductionmentioning
confidence: 99%